2010
DOI: 10.1080/00268976.2010.508472
|View full text |Cite
|
Sign up to set email alerts
|

Excited states of spherium

Abstract: We report analytic solutions of a recently discovered quasi-exactly solvable model consisting of two electrons, interacting {\em via} a Coulomb potential, but restricted to remain on the surface of a $\mathcal{D}$-dimensional sphere. Polynomial solutions are found for the ground state, and for some higher ($L\le3$) states. Kato cusp conditions and interdimensional degeneracies are discussed.Comment: 6 pages, 2 figures, to appear in Mol. Phy

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 66 publications
3
48
0
Order By: Relevance
“…One can note the similarity of the three-term recurrence relation obtained for R 1 = R 2 [10][11][12] and the term in square brackets in (17). The condition s 1 = 0 shows that the exact wave functions do not contain any term proportional to the interelectronic distance u.…”
Section: Exact Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…One can note the similarity of the three-term recurrence relation obtained for R 1 = R 2 [10][11][12] and the term in square brackets in (17). The condition s 1 = 0 shows that the exact wave functions do not contain any term proportional to the interelectronic distance u.…”
Section: Exact Solutionsmentioning
confidence: 99%
“…In a recent series of papers [10][11][12], we have found exact solutions for several new quasi-exactly solvable models. In particular, we have shown that one can solve the Schrödinger equation for two electrons confined to a ring [12] or to the surface of a sphere [10,11] for particular values of the ring or sphere radius.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the result of Pechukas who showed that, when two nodal surfaces cross, they are perpendicular at the crossing point. 38 We have recently shown that, for certain states such as the 3 P o (sp), 3 P e (p 2 ), 3 D e (sd) and 3 D o (pd) states, exact solutions of the Schrödinger equation can be found in closed form for specific values of the radius R. 39,40 Even though the exact closed-form expression of the Schrödinger equation is only known for particular values of the radius, their exact nodes are analytically known for all radii (see Table I). …”
Section: Proof Of the Exactness Of The Nodesmentioning
confidence: 99%
“…These are the 1 S e (s 2 ), 1 P o (sp), 1 D o (pd) and 1 F e (pf ) states. 40 These singlet states are connected to their triplet partner by exact interdimensional degeneracies. [40][41][42] Two states in different dimensions are said to be interdimensionally degenerated when their energies are the same.…”
Section: Interdimensional Degeneraciesmentioning
confidence: 99%